Four facets of learning in performance measurement. Issue 9 (19th November 2018) - Martin, Jason; Elg, Mattias; Wallo, Andreas; Kock, Henrik
Abstract : Purpose: The purpose of this paper is to contribute to a better understanding of the role of learning in performance measurement. Design/methodology/approach: The authors develop a theoretical framework combining workplace learning theory with purposes of performance measurement. The authors elaborate this framework empirically by identifying critical incidents from a case set within a context containing a broad range of different performance measurement activities. Finally, the authors discuss the results and the possible implications for using the theoretical framework in order to better understand facets of learning regarding the design of performance measurement. Findings: Workplace learning theory provides a deeper understanding of how the mechanisms of performance measurements support control or improvement purposes. The authors propose a tentative framework for learning as a driver for performance measurement and four facets of learning are identified: reproductive, rule-oriented, goal-oriented and creative learning. Research limitations/implications: The empirical material is limited to the healthcare context and further studies are needed in order to validate the findings in other settings. Practical implications: The authors argue that all managers must consider what kind of learning environment and what kind of learning outcomes best serve the interests of their organisation. Purposeful and carefully designed organisational arrangements and learning environments are more likely to induce intended learning outcomes. Originality/value: Previous connections between the fields of "performance measurement" and "workplace learning" often lack any deeper conceptualisations or problematisations of the concept of learning. In this paper, the authors provide a more nuanced discussion about the process of learning in performance measurement, which may provide a basis for further research and scholarly attention.